Natural biology and management of nonmuscle invasive bladder cancer. Issue 3 (May 2016) - Scarpato, Kristen R.; Tyson, Mark D.; Clark, Peter E.
Abstract : Purpose of review: This article reviews the natural biology of noninvasive bladder cancer and its management strategies while summarizing the most recent advances in the field. Recent findings: Nonmuscle invasive bladder cancer (NMIBC) has a tendency to recur and progress. Risk stratification has helped triage patients but improved tools, including biomarkers, are still needed. Enhanced endoscopy with photodynamic imaging, narrow band imaging, optical coherence tomography and confocal laser endomicroscopy show promise for diagnosis, risk stratification and disease monitoring. Attempts at better treatment, especially in refractory high-risk cases, include the addition of intravesical hyperthermia, combination and sequential therapy with existing agents and the use of novel agents such as mycobacterial cell wall extract. New data are emerging regarding the potential role of active surveillance in low-risk patients. Summary: NMIBC represents a variety of disease states and continues to pose management challenges. As our understanding of tumor biology improves and technology advances, achieving better outcomes through individualized care may be possible.